The immune response to sub-clinical mastitis is impaired in HIV-infected women - (:unkn) unknown (My University, 2018)
BACKGROUND : Subclinical mastitis (SCM) is relatively common in lactating women and may be associated with HIV shedding in breast milk. The potential association between HIV infection and breast milk immunologic factors and immune response to SCM needs to be addressed.METHODS : In this cross-sectional study, SCM (Na/K ratio > 1) was tested in 165 mature breast milk samples collected from 40 HIV-infected women who didn't transmit HIV to their child by breastfeeding and 43 HIV-uninfected women enrolled in an interventional cohort in South-Africa (Vertical Transmission Study). The level of 33 immune markers related to Th1/Th2 related response, inflammation and bacterial exposure were compared in ART-naive HIV-infected versus HIV-uninfected women. The associations between HIV infection and SCM on the concentration of immune factors were tested separately by Wilcoxon rank-sum test and corrected for false discovery rate. To control for potential confounder effects and take into account the clustering of breast milk samples from a single woman, multivariate mixed linear models adjusted on child age at the time of sampling were performed for each immune factor.RESULTS : Subclinical mastitis was detected in 15 (37.5%) HIV-infected women and 10 (23.3%) HIV-uninfected women. In the absence of SCM, the breast milk levels of IP-10 and MIG were higher and IL1-RA lower in HIV-infected women than in HIV-uninfected women (respectively p < 0.001, p = 0.001, p = 0.045). In HIV-uninfected women, SCM was characterized by a robust immune response with higher concentrations of a broad panel of Th1 and inflammatory related immune markers than in samples without SCM. By contrast, in HIV-infected women a limited number of immune markers were increased and lower increases were observed in samples with SCM than without SCM.CONCLUSION : HIV infection in ART-naïve women was associated with elevated breast milk levels of IP-10 and MIG, which areTh1-rel
Keywords: African Research